Management of a Buccal Space Mass: A Clinical Case Report - Alexander Karatzanis; Stylianos Velegrakis; Georgia Liva; Dionysios Kyrmizakis; Emmanuel Prokopakis (Case Reports in Otolaryngology)
Background. Buccal space tumors constitute rare pathologies with significant histological diversity. They may pose serious diagnostic and therapeutic challenges for the head and neck surgeon. Methods. A case of buccal space tumor diagnosed and treated in a tertiary center is presented. Clinical presentation, imaging, and surgical approach are discussed, followed by review of the literature. Results. A 79-year-old male patient with a slowly growing painless mass on the right cheek presented to a head and neck reference center. Imaging revealed a tumor of the right buccal space with nonspecific characteristics. Imaging studies revealed extended infiltration of the masseter muscle as well as the anterior border of the parotid gland. FNA biopsy was performed but was nondiagnostic. The decision of surgical excision with a modified parotidectomy incision was taken. The lesion was completely excised with preservation of neighboring facial nerve branches and ipsilateral Stensen’s duct. The postoperative course was uneventful. Histological examination showed CLL/Lymphoma, and the patient was referred to the hematology department for staging and further management. Conclusion. Differential diagnosis of buccal space masses is very diverse. Despite challenges in the diagnostic and therapeutic approach, these entities may be managed surgically with minimal morbidity.